2012
DOI: 10.1089/jwh.2011.2963
|View full text |Cite
|
Sign up to set email alerts
|

Yoga as a Complementary Treatment for Smoking Cessation in Women

Abstract: Yoga may be an efficacious complementary therapy for smoking cessation among women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 64 publications
1
106
0
1
Order By: Relevance
“…Randomization was stratified by high versus low nicotine dependence using the Fagerstrom Nicotine Dependence Scale (see "Measures") [35], to ensure even distribution across study conditions of highly nicotine-dependent men (score 7 and above). Participants in both the yoga and wellness conditions attended weekly 30-min individual sessions with a doctoral-level counselor as part of an 8-week CBT program for smoking cessation, which was based on our previous research [18] and that of others [36][37][38]. This program applied social cognitive theory [39] to smoking cessation, including self-monitoring stimulus control, coping with high-risk situations, stress management, and relaxation skills.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Randomization was stratified by high versus low nicotine dependence using the Fagerstrom Nicotine Dependence Scale (see "Measures") [35], to ensure even distribution across study conditions of highly nicotine-dependent men (score 7 and above). Participants in both the yoga and wellness conditions attended weekly 30-min individual sessions with a doctoral-level counselor as part of an 8-week CBT program for smoking cessation, which was based on our previous research [18] and that of others [36][37][38]. This program applied social cognitive theory [39] to smoking cessation, including self-monitoring stimulus control, coping with high-risk situations, stress management, and relaxation skills.…”
Section: Methodsmentioning
confidence: 99%
“…That pilot trial demonstrated a large effect size for smoking cessation for the group that received the yoga intervention (odds ratio=4.56) [18]. While yoga's growing popularity among women in the USA has been documented [19,20], we were unable to identify any research showing trends for men's yoga practice in the USA.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The practice of Yoga helps people quitting smoking, alcohol and many other kinds of addiction [30]. A recent study has indicated the efficacy of Yoga for gradually abstaining from the use of smoking [31].…”
Section: Relevance Of Yoga For De-addictionmentioning
confidence: 99%
“…While beneficial effects of exercise have been observed in both illicit drug-dependent males and females, few studies have included a large enough sample size to examine sex and hormonal differences in its efficacy. Results from several studies in smokers have examined the protective effects of exercise solely in females with results suggesting limited effectiveness due to poor exercise adherence during treatment (Marcus et al 2005;Marcus et al 1995) and inconsistent exercise conditions measured (Bock et al 2012;Roberts et al 2012;Ussher et al 2012; i.e. type, amount, and intensity).…”
Section: Dose-dependent Efficacy Of Exercise To Attenuate Cocaine-seementioning
confidence: 99%